The mediating effect of personality on mental workload and perceived professional benefits of nurses in East China - Ling Li; Zhixian Feng; Mingling Zhu; Jialu Yang; Lili Yang (BMC, 2023)
Abstract Background Nursing work is a work with high-stress load, and nurses with different personality may have different subjective feelings about their workload. Therefore, it is particularly necessary to comprehend the perceived professional benefits of nurses engaged in nursing work under high-pressure background, especially during the epidemic period. This study explored the relationship between mental workload, personality, and perceived professional benefits of nurses, and offer advices for the intervention of nurses with different personality to improve their perceived professional benefits. Materials and methods In this study, we used a cross-sectional study with a convenient sampling. 473 in-service nurses in Class A tertiary hospitals of Zhejiang Province were recruited by using the NASA Mission Load Index scale of nurses, the brief version of China's Big Five Personality Questionnaire, and the Nurses' perceived professional benefits questionnaire from July 2020 to March 2021. Sample size is 54.91%, and the response rate is 100%. Cronbach's alpha method was used to evaluate the reliability of the instruments. Descriptive statistical analysis was used to describe the socio-demographic data of the subject, and scores for research variables. The Mann-Whitney U-test, and Kruskal-Wallis H rank-sum test were used to compare the scores of perceived professional benefits with different demographic characteristics. Correlation analysis results were presented as the Spearman correlation coefficient. The plug-in v2.16.3 provided by SPSS software was used for linear regression analysis, and the deviation-corrected percentile Bootstrap method was used to examine the mediating role of personality (neuroticism, conscientiousness, agreeableness, openness and extroversion). Results Age, length of service in nursing, and record of formal schooling can affect nurses' perceived professional benefits. Mental workload, and perceived professional benefits were all above the median value. The mental workload was negatively correlated with perceived professional benefits (r= -0.129, P < 0.01), positively correlated with neuroticism (r = 0.242, P < 0.01), negatively correlated with agreeableness, openness, extroversion (r=-0.229~-0.221, P < 0.01), and negatively correlated with conscientiousness, but the differences were not significant. Nurses' perceived professional benefits were negatively correlated neuroticism (r=-0.109, P < 0.05), but positively associated with conscientiousness, agreeableness, openness, and extroversion (r = 0.098 ~ 0.326, P < 0.05). The mental workload can directly affect the perceived professional benefits in the direct effects, and can also affect the it through the mediating effect of agreeableness, extroversion, neuroticism, and openness. Conclusions Age, length of service in nursing, and record of formal schooling could affect nurses' perceived professional benefits, and personality played a partial mediating role in the influence of mental workload on the perceived professional benefits. The results of this study can provide strategies for nurses' human resource management. According to different demographic factors, and personality, various measures should be taken to guide nurses to evaluate the mental workload correctly, reduce their emotional pressure, increase job resources, and improve their perceived professional benefits.